Pemanfaatan Ampas Kelapa Hasil Dapur Rumah Tangga Menjadi Pangan Olahan - Rahmadewi, Yunda Maymanah; Hakika, Dhias Cahya; Sulistiawati, Endah; Salamah, Siti; Amelia, Shinta (UKInstitute, 2023)
Coconut dregs often become waste and garbage due to the lack of knowledge and skills of the community in utilizing the existing potential. Even though, coconut dregs still contain fiber which is good for the body. Activities using educating and training methods aimed to increase the knowledge and skills of the community in processing coconut dregs into processed food. Educating can increase participants' knowledge by 28.33 points. Training on processing sago cheese (sagu keju) from coconut dregs flour can improve skills in products that need to be equipped with a brand so that they have competitiveness in the market.